AN ANALYSIS OF STUDENTS’ COMPETENCE IN UNDERSTANDING ECONOMIC ENGLISH TERMS OF ACCOUNTING DEPARTMENT AT UMMU - Amrin Hi. Saban; Ratnasari A Manaf (JURNAL DODOTO, 2020)
ABSTRACT Economic terms have many words that used economic words. By economic terms, the accounting students can understand what they said, and can be seen that economic terms has different meaning with English language although economic terms used English language. The research was a qualitative research, this research aimed to know students competence in using English economic terms.. It was conducted at the third semester in accounting department at Muhammadiyah University of North Maluku. The subject on this research were 17 (seventeen) students, the instument in this reserach was worksheets. The researcher gave test to the students, after that the researcher collected the data of the students’ answer, then the researcher analyzed each students answer. Based on the data findings, the students got motivation to learning English economic terms. There were variations of students’ sentences. The first students can make a sentence with economic terms, the second, students found difficulties to know economic terms itself.